1971
DOI: 10.1037/h0031713
|View full text |Cite
|
Sign up to set email alerts
|

Clinical psychology training programs and minority groups: A survey.

Abstract: Describes results from a survey of 81 schools with clinical training program concerning their attitudes and actions with respect to minority group faculty and students. Data were analyzed according to (a) number of minority group faculty (mgf) by geographic region; (b) number of minority group students (mgs) by geographic region; (c) mgf compared to united states population; (d) mgs compared to united states population; (e) recruitment of mgs by region; and (f) distribution of number and percentage of theoreti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

1972
1972
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 15 publications
0
23
0
Order By: Relevance
“…Much of the ineffectiveness of community mental health programs may be due to their failure to recognize the unique cultural needs of minority groups and to implement procedures responsive to those needs. The training of minority mental health professionals has been emphasized as a possible approach to the problems of minority persons in psychotherapy (Boxley & Wagner, 1971). However any increased psychotherapeutic effectiveness of minority therapists with minority clients remains to be empirically demonstrated.…”
Section: H Newton Malony Fuller Theological Seminarymentioning
confidence: 99%
“…Much of the ineffectiveness of community mental health programs may be due to their failure to recognize the unique cultural needs of minority groups and to implement procedures responsive to those needs. The training of minority mental health professionals has been emphasized as a possible approach to the problems of minority persons in psychotherapy (Boxley & Wagner, 1971). However any increased psychotherapeutic effectiveness of minority therapists with minority clients remains to be empirically demonstrated.…”
Section: H Newton Malony Fuller Theological Seminarymentioning
confidence: 99%
“…The survey of minority group representation in clinical psychology by Boxley and Wagner, completed during the 1969-70 academic year, will serve as a basis for comparison and a base line for future studies. The questionnaire and the methods used in this survey are essentially the same as those in the Boxley and Wagner study (for survey results see Boxley & Wagner, 1971).…”
Section: The Questionnairesmentioning
confidence: 99%
“…Furthermore, the lack of participation by ethnic minorities in psychology (Boxley & Wagner, 1971) is interpreted by many to be indicative of unfair discrimination practices in the field. A survey undertaken by Wispe, Ash, Awkard, Hicks, Hoffman, and Porter (1969) found that (a) black psychologists were isolated from the mainstream of psychology and underrepresented as members in APA, (b) approximately half of those surveyed felt that race hindered their professional opportunities, and (c) many lacked faith in APA's willingness and ability to take corrective action in changing this situation.…”
Section: Psychology and The Establishmentmentioning
confidence: 99%